Crustal thickness and Vp/Vs ratio in NW Namibia from receiver functions: Evidence for magmatic underplating due to mantle plume‐crust interaction. Issue 9 (14th May 2015) - Heit, Benjamin; Yuan, Xiaohui; Weber, Michael; Geissler, Wolfram; Jokat, Wilfried; Lushetile, Bufelo; Hoffmann, Karl‐Heinz
Abstract A seismological network was operated at the junction of the aseismic Walvis Ridge with the northwestern Namibian coast. We mapped crustal thickness and bulk Vp/Vs ratio by the H‐k analysis of receiver functions. In the Damara Belt, the crustal thickness is ~35 km with a Vp/Vs ratio of <1.75. The crust is ~30 km thick at the coast in the Kaoko Belt. Strong variations in crustal thickness and Vp/Vs ratios are found at the landfall of the Walvis Ridge. Here and at ~150 km northeast of the coast, the crustal thickness increases dramatically reaching 44 km and the Vp/Vs ratios are extremely high (~1.89). These anomalies are interpreted as magmatic underplating produced by the mantle plume during the breakup of Gondwana. The area affected by the plume is smaller than 300 km in diameter, possibly ruling out the existence of a large plume head under the continent during the breakup.